Genomic Approaches Reveal an Endemic Subpopulation of Gray Wolves in Southern China - Wang, Guo-Dong; Zhang, Ming; Wang, Xuan; Yang, Melinda A.; Cao, Peng; Liu, Feng; Lu, Heng; Feng, Xiaotian; Skoglund, Pontus; Wang, Lu; Fu, Qiaomei; Zhang, Ya-Ping (iScience, 2019)
Although gray wolves (Canis lupus) are one of the most widely distributed terrestrial mammals, their origins in China are not well understood. We sequenced six specimens from wolf skins, showing that gray wolves from Southern China (SC) derive from a single lineage, distinct from gray wolves from the Tibetan Plateau and Northern China, suggesting that SC gray wolves may form a distinct subpopulation. Of SC gray wolves, one wolf from Zhejiang carries a genetic component from a canid and had gene flow from a population related to or further diverged from wolves than the dhole. This may indicate that interspecific gene flow likely played an important role in shaping the speciation patterns and population structure in the genus Canis. Our study is the first to survey museum gray wolves' genomes from Southern China, highlighting how sequencing the paleogenome from museum specimens can help us to study extinct species. [Display omitted] •Gray wolves from South China derive from a single lineage•A Zhejiang wolf shows admixture (∼12%–14%) from a deeply diverged canid species•Lowland gray wolf shows close genetic relationship to Tibetan Plateau gray wolves Biological Sciences; Genomics; Evolutionary Biology